Leucine aminopeptidase 3 promotes migration and invasion of breast cancer cells through upregulation of fascin and matrix metalloproteinases‐2/9 expression. Issue 3 (11th November 2018) - Fang, Chunyan; Zhang, Jian; Yang, Hanlin; Peng, Lili; Wang, Kun; Wang, Yanjie; Zhao, Xin; Liu, Huijie; Dou, Chunhui; Shi, Lihong; Zhao, Chunling; Liang, Shujuan; et al.
Abstract: Overexpression of leucine aminopeptidase 3 (LAP3) is involved in proliferation, migration, and invasion of several tumor cells and plays a crucial role in tumor metastasis. However, the related mechanism remains unknown. In this study, we used MDA‐MB‐231 and MCF7 breast cancer cell lines to explore the role of LAP3 in the regulation of cancer cell migration and invasion by employing the natural LAP3 inhibitor bestatin and a lentivirus vector that overexpresses or knocks down LAP3. Bestatin inhibited tumor cell migration and invasion in a dose‐dependent manner. Western blot assay showed that bestatin and knockdown of LAP3 upregulated phosphorylation of Hsp27 and downregulated expression of fascin. Phosphorylation of Akt and expression of matrix metalloproteinase‐2/9 can also be downregulated. LAP3 overexpression showed the opposite results. Immunohistochemistry analysis was conducted to detect expression levels of LAP3 in breast cancer tissues. High LAP3 expression was correlated with the grade of malignancy. Findings of this study uncovered the molecular mechanism of LAP3 on breast cancer metastasis and indicated that LAP3 may act as a potential antimetastasis therapeutic target. Abstract : Findings of this study uncovered that leucine aminopeptidase 3 (LAP3) promotes migration and invasion of breast cancer cells through the upregulation of fascin and matrix metalloproteinases‐2/9 (MMP‐2/9) expression and indicated that LAP3 may act as a potential antimetastasis therapeutic target.